Global cooperation among G20 Countries : responding to the crisis and restoring growth - Ghate, Chetan; Pickford, Stephen; Rathinam, Francis Xavier (Springer India Imprint: Springer, 2014)
At the outbreak of the global financial crisis, 2008, the G20 was widely acknowledged as helping prevent an even more serious decline in the global economy. It helped to calm the panic in financial markets and articulate a set of possible policy options to restore global stability and growth. However, as the dual-track recovery set in, policy options for advanced economies and EMEs diverged. Within this context, this book will explore the scope for cooperation amongst the G20 and the diverging challenges and the intricate interconnectedness of policy options between advanced economies and the EMEs within the G20.